Jurnal "Dinamika Administrasi Bisnis" - Pujianto, Agung (Jurnal Dinamika Administrasi Bisnis, 2016)
A purchase decision is taken after the consumer behavior through several processes, namely the introduction of the problem, information search and evaluation of alternatives. Consumer purchase decisions do not stop until the decision to shop alone, but will continue in the post-purchase behavior. There are several factors that influence the consumer’s decision to shop. However, in this study only took three factors, namely the price, variety of products and services.This study aims to identify and analyze the effect of prices, variety of products and services to the purchasing decision at Boutique D’Cheapest. The data used are primary data through questionnaires. The sampling technique used purposive sampling method is calculated through a formula Slovin. Samples taken as many as 65 respondents. The population in this study are all consumers at Boutique D’Cheapest. Test used to test the research instrument is a form of validity, reliability, and classical assumption. Furthermore, quantitative data analysis performed by multiple linear regression analysis using SPSS 20 for windows.Results of this study stated that the price variable has a positive effect and does not significantly influence the purchasing decision Boutique D’Cheapest, while the variable range of products and services and a significant positive influence on purchasing decisions at Boutique D’Cheapest.